2004
DOI: 10.1159/000077106
|View full text |Cite
|
Sign up to set email alerts
|

NuMA Expression and Function in Mouse Oocytes and Early Embryos

Abstract: Nuclear mitotic apparatus protein (NuMA), originally described as a nuclear protein, is an essential component in the formation and maintenance of mitotic spindle poles. In this study, we analyze the expression pattern and function of NuMA in mouse oocytes and early embryos. In germinal vesicle-stage oocytes, NuMA was detected both at the centrosome and in the nucleus. However, after nuclear maturation and extrusion of the first polar body, NuMA was concentrated at the broad meiotic spindle poles and at cytast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
2
2
0
1
Order By: Relevance
“…We first confirmed that NuMA was present in mouse oocytes (17). NuMA was diffusely positioned early in MI, but within 4 h of meiotic entry, it was concentrated at spindle poles concomitantly with their formation (Fig.…”
Section: Resultssupporting
confidence: 61%
“…We first confirmed that NuMA was present in mouse oocytes (17). NuMA was diffusely positioned early in MI, but within 4 h of meiotic entry, it was concentrated at spindle poles concomitantly with their formation (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The NuMA foci were translocated from the condensed chromosomes and became aligned at both poles of the meiotic spindle during the metaphase I and II stages. Comparing with previous studies, we found that NuMA distribution in rabbit species is similar to pig (Lee et al 2000) but different from mouse (Lee et al 2000, Tang et al 2004. In mouse oocytes, NuMA was localized along spindle microtubules (Lee et al 2000) and at cytasters (Tang et al 2004).…”
Section: Discussionsupporting
confidence: 53%
“…In previous studies, the researchers analyzed the expression pattern and function of NuMA in mouse and pig oocytes (Lee et al 2000) and early embryos (Tang et al 2004) as well as mouse (Zhong et al 2005, Van Thuan et al 2006 and pig cloned embryos. But the dynamic changes of NuMA and microtubules during meiosis I-II transition in rabbit oocytes have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, as has been revealed by immunolocalization studies mostly during mouse oogenesis, PCM proteins, including γ-tubulin, pericentrin, and NuMA are not eliminated during meiotic stages but show a dynamic redistribution. NuMA is a nuclear matrix protein which plays an important role in establishment and maintenance of the bipolar spindle apparatus (Maro et al, 1985;GuethHalonet et al, 1993;Calarco, 2000;Carabatsos et al, 2000;Lee et al, 2000;Can et al, 2003;Meng et al, 2004;Tang et al, 2004;Sedo et al, 2011). 4-D imaging in live maturing mouse oocytes revealed, that numerous acentrosomal MTOCs, spread in the ooplasm, then assemble into the functional acentrosomal meiotic spindle (Schuh and Ellenberg, 2007).…”
Section: Centrosomes In Germ Cellsmentioning
confidence: 99%